Severe bleeding of colonic origin - Mañana, Julio; Guicheff, Vladimir (Cirugía del Uruguay, 1971)
Serious colonic hemorrhages constitute an infrequent complication, but when they appear it is a grave emergency. They are somewhat more predominant in males, most frequently in aged persons. 69 % of the cases present intense acute anaemia; the remaining 31 % , modera te anaemia. It is easy to establish a diagnosis of hemorrhage but not a topographic diagnosis. Far this purpose it is useful to have tbe case hlstory; gastric probes are more adequa e than radiological study of the gastroduodenum. Radiological study of colon through ingestion is useful in discarding hemorr hages of the final intestinal loops; that of the colon by enema helps diagnosis in 60 % of cases. This is not the case with rectosigmoidoscopy and rectal tactile examination which serve to discard lesions of the anal canal. Two causes stand out in serious colonic hemorrhage: diverticular colopathy in the form of diverticular and colonic hemorrhagic arteriolopathies. The latter is more serious than diverticular colopathy because it affects patients with grave vascular liability and because there is direct bleeding of a vessel of important diameter with arteriosclerotic lesions. In such cases the procedure followed is an intense medica} treatment, but if this fails, surgery is employed. The following maneuvers described as complementary to the surgical act, performed in .order to establish the original site of the hemorrhage, were not satisfactory when we employed them: rectosigmoidoscopy with the assistence of the surgeon; intraoperatory coloscopy and segmentary intestinal lavage. The ideal treatment for these lesions is segnientary resection, but if the lesion is not found the surgeon should remember that he can resort to derivation colostomy, before effecting total colectomy.